A COVID question: the impact on our nursing home residents (UCC Student Medical Journal, 2024)
COVID-19, a novel coronavirus which targets the respiratory system, has had a significant impact on Irish nursing homes. The virus was declared a global pandemic in March 2020, and as of 14th June the Health Protection Surveillance Centre has reported 258 clusters of cases in nursing homes, comprising 21% of all cases in Ireland and associated with 943 deaths. This pandemic is a source of many ethical dilemmas — an example being the ethical issues arising from enforced social isolation imposed on residents during lock-down.The cocooning of residents in nursing homes raises a question with no simple answer — does the risk this isolation poses to the wellbeing of elderly residents outweigh the benefits of such strict measures to protect them from COVID-19?The adverse effects of isolation, although relevant in any infectious outbreak, are compounded in this instance by the unprecedented scale of the coronavirus pandemic and the immense pressure on the healthcare system as it faces this new threat to health. Even in the chaos of a global pandemic, the ethical principles at the root of all healthcare decisions, namely non-maleficence, beneficence, autonomy, and justice remain pertinent.
Keywords: COVID; nursing home; COVID-19